A MICRO ANALYSIS STUDY OF PRAGMATIC CONTENT IN INDONESIAN ELT TEXTBOOKS - Pramono, Satrio Aji; Kurniawan, Eri (IKIP PGRI Pontianak, 2020)
This study aims to explore the frequency of pragmatic content occurrence represented as speech acts of thanking and apologizing in two Indonesian ELT textbooks: a prescribed textbook published by Ministry of National Education and a commercial textbook. Pragmatic content of two ELT Textbooks entitled When English Rings the Bell and English on Sky were analyzed using Martinezâ€™s Framework on Speech act of thanking and apologizing. The result indicated that a number of speech acts of thanking and apologizing have sufficiently provided by both prescribed and commercial textbook. However, while there are various strategies which can be used to perform speech acts of thanking and apologizing, both textbooks failed to take into account the inclusion of those strategies. It is therefore advisable for language teachers to employ other authentic language sources to enhance learnersâ€™ pragmatic competence.Â